Covalent template-directed synthesis of a spoked 18-porphyrin nanoring - Majewski, M; Stawski, W; Van Raden, J; Clarke, M; Hart, J; O'Shea, J; Saywell, A; Anderson, HL (Wiley, 2023)
Rings of porphyrins mimic natural light-harvesting chlorophyll arrays and provide insights into electronic delocalization, providing a motivation for creating larger nanorings with closely spaced porphyrin units. Here, we demonstrate the first synthesis of a macrocycle consisting entirely of 5,15-linked porphyrins. This porphyrin octadecamer was constructed using a covalent six-armed template, made by cobalt-catalyzed cyclotrimerization of an H-shaped tolan with porphyrin trimer ends. The porphyrins around the circumference of the nanoring were linked together by intramolecular oxidative meso-meso coupling and partial β-β fusion, to give a nanoring consisting of six edge-fused zinc(II) porphyrin dimer units and six un-fused nickel(II) porphyrins. STM imaging on a gold surface confirms the size and shape of the spoked 18-porphyrin nanoring (calculated diameter: 4.7 nm).